1993
DOI: 10.1111/j.1365-3121.1993.tb00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Eocene age of eclogite metamorphism in Pakistan Himalaya: implications for India‐Eurasia collision

Abstract: A geochronological investigation of two rocks with an eclogitic assemblage (omphacite-garnet-quartz-rutile) from the High Himalaya using the Sm/Nd, Rb/Sr, U/Pb and AdAr methods is presented here. The first three methods outline a cooling history from the time of peak metamorphism at 49k6 Ma recorded by S d N d in garnet-clinopyroxene to the closure of Rb/Sr in phengite at 4 3 f l Ma and U/Pb in rutile at 39-40 Ma. The Sm/Nd isotopic system was fully equilibrated during eclogitization and has not been disturbed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 204 publications
(104 citation statements)
references
References 20 publications
8
95
0
Order By: Relevance
“…The range of the U/Pb ages indicates a protracted episode as long as 25 Myr for regional metamorphism of the host rocks at deep crust, i.e., a process from continental collision to postcollisional reworking. The upper U/Pb age limit yielded by the zircon rims in this study is consistent with the U/Pb ages of 44±3 Ma for the rim of zircon with a Permian core, a garnet-omphacite Sm-Nd isochron age of 49 ± 6 Ma, a phengite Rb-Sr isochron age of 43 ± 1 Ma for the Kaghan eclogite in Pakistan (Tonarini et al, 1993) as well as a U/Pb age of 50 Ma for overgrown quartz-bearing rims and a U/Pb age of 46 Ma for coesite-bearing rim (Kaneko et al, 2003;Parrish et al, 2006). The long episode of 40-50 Myr is common for high-pressure (HP) to ultrahigh-pressure (UHP) metamorphism in continent-continent collisional orogens such as the Dabei-Sulu in China and the Western Gneiss Region in Norway, whereas the short episode of 5-10 Myr is prominent in arc-continent collisional orogens such as the Himalayas and Alps (Zheng, 2012;Zheng et al, 2013).…”
Section: U/pb Ages Of Zircon Rims and (U-th)/he Ages Of Zirconssupporting
confidence: 62%
“…The range of the U/Pb ages indicates a protracted episode as long as 25 Myr for regional metamorphism of the host rocks at deep crust, i.e., a process from continental collision to postcollisional reworking. The upper U/Pb age limit yielded by the zircon rims in this study is consistent with the U/Pb ages of 44±3 Ma for the rim of zircon with a Permian core, a garnet-omphacite Sm-Nd isochron age of 49 ± 6 Ma, a phengite Rb-Sr isochron age of 43 ± 1 Ma for the Kaghan eclogite in Pakistan (Tonarini et al, 1993) as well as a U/Pb age of 50 Ma for overgrown quartz-bearing rims and a U/Pb age of 46 Ma for coesite-bearing rim (Kaneko et al, 2003;Parrish et al, 2006). The long episode of 40-50 Myr is common for high-pressure (HP) to ultrahigh-pressure (UHP) metamorphism in continent-continent collisional orogens such as the Dabei-Sulu in China and the Western Gneiss Region in Norway, whereas the short episode of 5-10 Myr is prominent in arc-continent collisional orogens such as the Himalayas and Alps (Zheng, 2012;Zheng et al, 2013).…”
Section: U/pb Ages Of Zircon Rims and (U-th)/he Ages Of Zirconssupporting
confidence: 62%
“…One possible interpretation is the incorporation of excess Ar. Several studies on highpressure white micas indicated that Ar-Ar ages are geologically meaningless due to excess Ar (Tilton et al 1991;Tonarini et al 1993;Li et al 1994;Arnaud and Kelley 1995;Hacker and Wang 1995). Li et al (1994) and Boundy et al (1997) suggested that excess Ar in Phe is mainly observed in Bt-free UHP-HP rocks.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this study was to investigate Ar isotope systematics of garnet and fluid inclusions in garnet, with the specific aim of studying excess 40 Ar by the 40 Ar/ 39 Ar crushing technique given that age scatter attributed to excess 40 Ar is ubiquitous in the (U)HP metamorphic rocks of Dabieshan , the Seward Peninsula of Alaska (Hannula and McWilliams, 1995), the western Alps (Scaillet et al, 1992;Arnaud and Kelley, 1995;Ruffet et al, 1995Ruffet et al, , 1997Scaillet, 1996), the Holsnoy Island of western Norway (Boundy et al, 1997), the Pakistan Himalaya (Tonarini et al, 1993), and the Tavsanli Zone of NW Turkey (Sherlock and Arnaud, 1999;Sherlock and Kelley, 2002).…”
Section: Argon Isotope Systematics Of (U)hp Metamorphic Rocksmentioning
confidence: 99%